(untitled) (Modern American Journal of Social Sciences and Humanities, 2026)
This article discusses the methodology for developing students’ observational skills and spatial thinking in the process of pencil drawing classes. Pencil drawing is one of the main practical areas of fine arts education, which forms the skills of students to correctly perceive the shape, size, proportions, constructive structure, light-shadow relationships and spatial location of objects. The article reveals the educational significance of drawing based on observation, analyzing nature, determining the ratio and distance between objects, following the laws of perspective, and compositional placement.